Integrated Solid Waste Management for Closed Community: An Experiment on Jahangirnagar University Campus - Hossain, Md. Jakir; Mahmud, Md. Munir; Moinuddin, Golam (Waste Technology, 2023)
This study examines community participation in integrated solid waste management (ISWM) at Jahangirnagar University in Bangladesh. The university faces significant challenges in waste management, with negative social, environmental and economic consequences. The goal is to identify barriers to community involvement in ISWM and provide recommendations for enhancing engagement. The research uses a mixed-methods approach, surveying 397 respondents using cluster random sampling from the university's population of 20,000. Data collection methods include interviews, observations, focus groups, and document analysis. The findings highlight obstacles to community participation, such as limited community empowerment, mobilization, organization, and resource coordination. Household waste segregation is practiced by only 30% of respondents. However, 74% of participants express willingness to oversee door-to-door waste collection and dispose of waste at designated points, influenced by socioeconomic factors. Non-compliance with ISWM regulations is observed in 26% of respondents, and 12% lack sufficient knowledge about ISWM, indicating a need for improved organization and coordination. Additionally, some university authorities rely on outdated methods, resulting in weak enforcement of environmental regulations. Ineffective policies exacerbate the situation, failing to align with the market economy. The study recommends fostering cooperation between university authorities and the community, revising and enforcing regulations, and emphasizing waste generators' responsibility for proper disposal. Addressing these challenges can significantly improve solid waste management and environmental outcomes at Jahangirnagar University.